Food culture in Belgium - Scholliers, Peter (Food culture around the world., 2009)
Belgian food and drink receive much deserved attention in this thorough overview. The author covers essential information in the topical chapters on history, major foods and ingredients, cooking, typical meals, special occasions, eating out, and diet and health.